Can a pre-assessment help us to properly manage controversial risks of chemicals? A discussion on potential improvement of the REACH restriction process. Issue 8 (13th September 2016) - Devilee, Jeroen; Verhoeven, Julia; Beekman, Martijn; Knol, Anne B.
Abstract : The REACH regulation has been adopted to regulate the safe use of chemicals in Europe. One of the instruments of this regulation is the restriction of chemicals that cause unacceptable risks. A Member State can prepare a dossier to propose the restriction of the placing on the market or use of a substance. Up to now, seven restriction proposals have been evaluated, based primarily on the best scientific information available (predominantly on the Risk Assessment, RA). Experience with one of these dossiers, on phthalates, has learned that dossiers that are very uncertain, contested or ambiguous would, in addition to the RA, benefit from a Socio-Economic Analysis (SEA). This may avoid prolonged concern and societal debate among European citizens and scientists and prevents improper or incomplete informed decision-making. For ambiguous risks like phthalates, the use of a more extensive SEA in addition to the RA might help to weigh all relevant aspects in the subsequent decision-making. The use of (extensive) SEA does not seem necessary for all types of risks. Therefore, we argue that the REACH restriction process would benefit from a pre-assessment in which the type of risk to be managed is characterized. The subsequent evaluation process can then be designed according to the type of risk at hand.